口腔苔癬様病変11例の臨床的・病理組織学的検討 - 河野, 通良; 野村, 武史; 橋本, 和彦; 稲田, 潤一郎; 髙橋, 慎一; 松浦, 信幸; 秋山, 友理恵; 三邉, 正樹; 青木, 勇介; 森田, 奈那 (日本口腔外科学会雑誌, 2023)
Oral lichenoid lesion (OLL) is a lesion that causes cell-mediated immune tissue reactions, and is very similar to oral lichen planus (OLP). This disease can be distinguished from OLP when the cause is clear. OLL is often caused by dental metals, drugs and diseases such as graft-versus-host disease(GVHD). The clinical and histopathological differences between OLP and OLL are still under debate. In this study, the clinical and histopathological findings of 11 cases of OLL were retrospectively investigated.　The study included 11 patients who visited the outpatient clinic for oral mucosal diseases(joint outpatient clinic for oral surgery and dermatology) at the Tokyo Dental College Ichikawa General Hospital and were diagnosed with OLL in cooperation with dermatologists between April 2014 and March 2019. The patients included four males and seven females, with an average age of 56.9 years. Lesions were associated with drugs (4 cases), materials (3 cases), GVHD(2 cases), dental material(1 case) and hepatitis C (1 case). OLL lesions were in the buccal mucosa (9 cases), gingiva (8 cases), dorsum of the tongue(8 cases), lip(6 cases) and sublingual surface (6 cases). The clinical classifications were red type (6 cases) and white type(5 cases), with 6 cases including skin symptoms. Lesions were found in 4.7 sites on average.　Histopathological findings were consistent with OLP in 11 cases, and no findings characteristic of OLL were observed.　Immunohistochemical staining for p53 and Ki-67 (carcinogenesis markers) was performed; however, no epithelial positive cell overlay was observed in any of the cases.